YKL-40 Aggravates Early-Stage Atherosclerosis by Inhibiting Macrophage Apoptosis in an Aven-dependent Way - Huan, Wei; Yandong, Liu; Chao, Wang; Sili, Zou; Jun, Bai; Mingfang, Liao; Yu, Chen; Lefeng, Qu (Frontiers in Cell and Developmental Biology, 2021)
Objective: PrCR (programmed cell removal) in atherosclerotic plaques plays a crucial role in retarding lesion progression. Macrophage apoptosis has a critical role in PrCR, especially in early-stage lesions. YKL-40 has been shown to be elevated as lesions develop and is closely related to macrophages. This study aimed to determine the effect of YKL-40 on regulating macrophage apoptosis and early-stage atherosclerosis progression. Research design and methods: The correlations among the expression level of YKL-40, the area of early-stage plaque, and the macrophage apoptosis rate in plaques have been shown in human carotid atherosclerotic plaques through pathological and molecular biological detection. These results were successively confirmed in vivo (Ldlr-/- mice treated by YKL-40 recombinant protein/neutralizing antibody) and in vitro (macrophages that Ykl40 up-/down-expressed) experiments. The downstream targets were predicted by iTraq analysis. Results: In early-stage plaques, the YKL-40 expression level had a significant positive correlation with the area of the lesion and a significant negative correlation with the macrophage apoptosis rate. In vivo, the plaque area of aortic roots was significantly larger in the recomb-YKL-40 group than that in IgG group (P=0.0247) and was significantly smaller in the anti-YKL-40 group than in the IgG group (P=0.0067); the macrophage apoptosis rate of the plaque in aortic roots was significantly lower in the recomb-YKL-40 group than that in IgG group (P=0.0018) and was higher in anti-YKL-40 group than that in VC group. In vitro, the activation level of caspase-9 was significantly lower in RAW264.7 with Ykl40 overexpressed than that in controls (P=0.0054), while the expression level of Aven was significantly higher than that in controls (P=0.0031). The apoptosis rate of RAW264.7 treated by recomb-YKL40 was significantly higher in the Aven down-regulated group than that in the control group (P<0.001). The apoptosis inhibitor Aven was confirmed as the target molecule of YKL-40. Mechanistically, YKL-40 could inhibit macrophage apoptosis by upregulating Aven to suppress the activation of caspase-9. Conclusion: YKL-40 inhibits macrophage apoptosis by upregulating the apoptosis inhibitor Aven to suppress the activation of caspase-9, which may impede normal PrCR and promote substantial accumulation in early-stage plaques, thereby leading to the progression of atherosclerosis.